2020
DOI: 10.12700/aph.17.7.2020.7.8
|View full text |Cite
|
Sign up to set email alerts
|

Selected Problems of Family Business: A Case Study from Slovakia

Abstract: The scientific paper deals with a part of the business sector, which is made up of family businesses. The paper presents the current status of such businesses from the perspective of positive and negative factors which will be linked to the problem areas. In this article, we have focused our attention on some aspects of family business, especially the managerial aspects, because the management of a family business has various differences and specifics compared to other types of businesses. In the theoretical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This longer time horizon also allows family owners to tolerate an increased deficit to encourage company's management to participate in research and development (R&D) investment strategies (Asensio-Lopez et al 2019). Research by authors Peracek et al (2020) identified the following innovation factors within the family businesses: product quality and services, customer relationship management, customer requirements, proactive approaches in marketing, and employee qualification.…”
Section: Introductionmentioning
confidence: 99%
“…This longer time horizon also allows family owners to tolerate an increased deficit to encourage company's management to participate in research and development (R&D) investment strategies (Asensio-Lopez et al 2019). Research by authors Peracek et al (2020) identified the following innovation factors within the family businesses: product quality and services, customer relationship management, customer requirements, proactive approaches in marketing, and employee qualification.…”
Section: Introductionmentioning
confidence: 99%
“…the lack of jobs at the employer, may lead to a situation where the goal of reassigning an employee within the framework of the employment contract cannot be achieved. Peráček et al (2020) see the solution in the legal possibility of reassigning the employee but only in specific cases and in agreement with him for work of a different kind than agreed in the employment contract. At the same time, however, the employer must ensure that the work assigned to the employee corresponds to his/her fitness for work and is suitable for him in terms of his or her abilities and qualifications.…”
Section: Agreement On Changing Working Conditionsmentioning
confidence: 99%
“…Nabi (2000) defined career-oriented motivation as advancement motivation and the importance of the job. This means that a career-oriented person has a strong desire for professional growth and as a result of this he gets a higher level of satisfaction from work (Peracek et al, 2020). According to Karácsony and Machová (2015), there are numerous critical factors to a successful motivation system.…”
Section: Literature Reviewmentioning
confidence: 99%